2022
DOI: 10.1177/1759720x221114104
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of exercise on pain symptoms, clinical inflammatory markers and inflammatory cytokines in people with rheumatoid arthritis: a systematic literature review

Abstract: Background: Exercise is advocated in the treatment of rheumatoid arthritis (RA). However, uncertainty around the acute effects of exercise on pain and inflammation may be stopping people with RA from exercising more regularly. Objectives: To determine the acute effects of exercise on pain symptoms, clinical inflammatory markers, and inflammatory cytokines in RA. Design: A systematic review of the literature. Data sources and methods: Five databases were searched (PubMed, Cochrane Library, CINAHL, Scopus and SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…Finally, Coelho-Oliveira AC et al [ 48 ] investigated the effect of acute whole-body vibration exercise under the hands, on handgrip strength, range of motion, and electromyography signals of women with RA, and demonstrated that it promotes neuromuscular modifications during the handgrip of women with stable RA. On the contrary, a recent systematic literature review that investigated the acute effects of exercise on pain symptoms, clinical inflammatory markers, and inflammatory cytokines in RA concluded that post-exercise responses for pain, clinical inflammatory markers and inflammatory cytokines were not different between people with or without RA [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Coelho-Oliveira AC et al [ 48 ] investigated the effect of acute whole-body vibration exercise under the hands, on handgrip strength, range of motion, and electromyography signals of women with RA, and demonstrated that it promotes neuromuscular modifications during the handgrip of women with stable RA. On the contrary, a recent systematic literature review that investigated the acute effects of exercise on pain symptoms, clinical inflammatory markers, and inflammatory cytokines in RA concluded that post-exercise responses for pain, clinical inflammatory markers and inflammatory cytokines were not different between people with or without RA [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, inflammatory cytokine level decreases within a few hours after an exercise (83,84). However, evidence of the acute effect of exercise on inflammatory response in patients with RA is inconsistent (85). Two observational studies examined the acute effect of a single-session exercise on inflammatory cytokine (e.g., IL-6) in patients with RA; one of the studies found no significant change in IL-6 (86), whereas the other observed IL-6 level sharply increased in the first one hour, then gradually decreased, and returned to pre-exercise level in 24 hours (87).…”
Section: Inflammatory Response and Inflammatory Factorsmentioning
confidence: 99%
“…Throughout the course of the pathology, bone erosion occurs and predominantly surrounds the peripheral synovial joints. The clinical symptoms of RA include pain, edema development, and tenderness of the synovial joints located symmetrically and peripherally [3]. A great deal of progress has been made in the treatment of RA with antagonists of proinflammatory cytokines, such as tumor necrosis factor (TNF), interleukin-6 (IL-6), and IL-1β.…”
Section: Introductionmentioning
confidence: 99%